Fintech As A Financing Solution For Micro, Small and Medium Enterprises - Sabda Maulana; Nasution, Iskandar Mustofa; Shino3, Yamato; S.Panjaitan, Arop Ria (Pandawan Sejahtera Indonesia, 2022)
In 2020, more than 50 new fintech enterprises were formed, these financial businesses competing with the other 140s of startups that had previously been in the Indonesian financial scene. The fintech business in Indonesia has become a prima donna, attracting a lot of attention from financial industry players. Fintech startup investment has sparked a lot of interest, and several startups have even received series A funding this year. Fintech is only getting started, and there are a lot of new products coming out. In the interim, the Service of Cooperatives and Little and Medium Organizations (Service of Little and Medium Endeavors) has sent off 3.81 million miniature, little, and medium undertakings (SMEs) that are now utilizing a web-based stage to advertise their items. This records for around 8% of Indonesia's complete 58.9 million little and medium-sized organizations. The lack of access to capital is a long-standing issue that has hampered the growth of SMEs that do not have access to bank finance. SMEs are unable to create innovations to enhance output due to a lack of financial resources. However, the increasing expansion of fintech financing businesses, such as peer-to-peer lending, has opened up another option for loan funders. Peer-to-peer lending is a type of lending that focuses on the medium and lower market segments.